POH1 deubiquitinates pro-interleukin-1β and restricts inflammasome activity - Li Zhang (Nature Portfolio, 2018)
The inflammasomes are important for activating the pro-inflammatory cytokine interleukin-β (IL-1β) for protection against pathogens. Here the authors show that a deubiquitinase, POH1, reduces the conversion of pro-IL-1β into its active form, with in vivo data further implicating a role of POH1 for maintaining immune homeostasis.